Analisis Perhitungan Harga Pokok Produksi Untuk Kebijakan Harga Jual Dengan Pendekatan Full Costing Pada Roti Gembong Happy Di Samarinda - Mia Audina, Nurleni; Rachma Utary, Anis; Iskandar, Iskandar (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Nurleni Mia Audina, 2018. Analisys Calculation Of The Costs Of Goods Manufactured For Sale Price Policy With Full Costing Approach On Roti Gembong Happy In Samarinda. Guided by Ms. Anis Rachma Utary as the first supervisor and Mr. Iskandar as the second supervisor. The research aimed to analyze calculation of the costs of goods manufactured  for sale price policy on Roti Gembong Happy using the full costing approach. This research was done on Roti Gembong Happy in Samarinda, with the research object focused on roti original with production cost data in January 2018. The data collection techniques used in this research were interviews and observation. The research method with descriptive quantitative approach. The collection of cost of goods manufactured that has been used is cost process method, whilst the calculation of cost of goods manufactured using full costing approach for his sale price policy. The result of cost of goods manufactured according to the company’s method and full costing method has a difference that lies in the elements of factory overhead costs. The factory overhead costs according to the company’s method is Rp8.740.000,00, while according to full costing method, the factory overhead costs is Rp14.535.261,00 and for the cost per item according to the company is Rp3.845,38 and for the cost per item according to full costing method is Rp3.873,09. Therefore, the cost of goods manufactured, using full costing method, produces a selling price Rp8.000,00 per one roti original. The conclution of this research is that the calculation of cost of goods manufactured, that has been done by owner Roti Gembong Happy, has not specified in detail the costs that included in the production process, the cost that haven’t been included is fixed assets depreciation expense. The cost it is element important in calculation the factory overhead costs. The authors provide suggestions should the company in calculating of the cost of goods manufactured for sale price policy using the full costing approach because portraying costs more detail in include all the components of the cost of used during the production process takes place.